Respuesta :

Answer:

  1. (x, y, z) = (-5, -1, 0)
  2. (x, y, z) = (-8, -7, 5)

Step-by-step explanation:

1. A graphing calculator or equation-solving web site can tell you the solution is (-5, -1, 0).

As is sometimes the case with multiple-choice questions, you can choose the "consensus answer".

For x, -5 appears in 3 of 4 answer choices.

For y, -1 appears in 3 of 4 answer choices.

For z, 0 appears in 3 of 4 answer choices.

Thus, the "consensus" is that the answer is (-5, -1, 0). Choosing this one to check can shorten the work of checking the answer choices.

  • -5 +5(-1) +4(0) = -10 . . . first equation can use this answer
  • 2(-5) -(-1) +5(0) = -9 . . . second equation can use this answer
  • 2(-5) -10(-1) -5(0) = 0 . . . third equation can use this answer

So, by "guess and check" we have determined the solution to be (-5, -1, 0).

__

2. First of all, you can substitute the given value of z into the other two equations. Then you have ...

  • 2x -y +5 = -4
  • -2x +3y -5 = -10

The first of these equations can be solved for y:

  y = 2x +9

and this can be substituted for y in the second of these equations:

  -2x +3(2x +9) -5 = -10

  4x +22 = -10

  4x = -32

  x = -8

and ...

  y = 2(-8) +9 = -7

So this solution, too, is the "consensus solution," ...

  (x, y, z) = (-8, -7, 5)